2010
DOI: 10.1089/jpm.2010.0140
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Falls among Cognitively Intact Hospice Patients

Abstract: The current model predicted fall occurrence far better than the Morse Falls Scale and other functional status measures and may lead to a shift in fall prevention approaches among hospice patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Interestingly, we found that Fallers with a dementia diagnosis fell about 18 days after admission, while non-dementia Fallers fell at about 28 days, suggesting that a fall risk reassessment should occur at approximately weeks two-three, depending on primary diagnosis and irrespective of clinical or cognitive decline, medication changes or any other factor that would increase fall likelihood. Furthermore, our analysis found that the contributing significance of each fall assessment variable was commensurate with other studies 2 3 5 10 18 20 27…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, we found that Fallers with a dementia diagnosis fell about 18 days after admission, while non-dementia Fallers fell at about 28 days, suggesting that a fall risk reassessment should occur at approximately weeks two-three, depending on primary diagnosis and irrespective of clinical or cognitive decline, medication changes or any other factor that would increase fall likelihood. Furthermore, our analysis found that the contributing significance of each fall assessment variable was commensurate with other studies 2 3 5 10 18 20 27…”
Section: Discussionsupporting
confidence: 88%
“…Mitigation or management of these risks resulted in an adjusted risk ratio (ARR) of 0.82 (0.72-0.94) of falling and improved adjusted incidence rate ratio of falling monthly to 0.63 (0.49-0.83). 12 Exercise also improved fall risk (ARR: 0.86; 0.75-0.99). Types of exercise programs varied but included general aerobic or endurance activities as well as targeted training of balance, gait, and strength.…”
Section: Functional Mobilitymentioning
confidence: 95%
“…13 Other factors contributing to falls in patients with advanced cancer or on hospice include mood disorder, brain tumor or metastasis, cancer-related pain, and history of falls. 10,12…”
Section: Functional Mobilitymentioning
confidence: 99%
“…Geriatric falls is a serious public health problem [25]. Living alone, effect of medications, movement disorders, weak sensory power, reduced mobility, and arthritis are risk factors for falls in the elderly population even if physically active [26][27][28]. UAE has a fast aging population compared with the other Gulf countries [29].…”
Section: Discussionmentioning
confidence: 99%